Planning Water Resources in Latin America and the Caribbean - Guzmán-Arias, Isabel (2013)
The current status of water resources management and planning in Latin America and the Caribbean countries is described and discussed. The analysis is based on recent studies made on this subject. The available information is updated and duly verified the reality of legislation, institutions and organizations in the countries of the region. Currently planning and integrated management of water resources have been characterized by great diversity of approaches for the legal and institutional aspects. These processes are anticipated by long debates and constant proposals to reform the few approved water laws (Dourojeanni & Jouravlev, 2002). Some countries like Mexico and Chile have more successful experiences conducive to achieving important goals, however, they still require the necessary continuity in time and coverage and nowadays are only isolated cases.